Generation of Transgenic Cloned Buffalo Embryos Harboring the EGFP Gene in the Y Chromosome Using CRISPR/Cas9-Mediated Targeted Integration - Zhao, Xiuling; Nie, Junyu; Tang, Yuyan; He, Wengtan; Xiao, Kai; Pang, Chunying; Liang, Xianwei; Lu, Yangqing; Zhang, Ming (Frontiers in Veterinary Science, 2020)
Sex control technology is of great significance in the production of domestic animals, especially for rapidly breeding water buffalo, which is an economically important species and served as a research model in the present study. We have confirmed that a fluorescence protein integrated in the Y chromosome is fit for sexing pre-implantation embryos in mouse. Firstly, we optimized the efficiency of targeted integration of exogenous gene encoding enhanced green fluorescent protein (eGFP) and mCherry in Neuro-2a cells, mouse embryonic stem cells, mouse embryonic cells (NIH3T3), buffalo fetal fibroblast (BFF) cells. The results showed that a homology arm length of 800 bp on both sides of the target is more efficient that 300 bp or 300 bp/800 bp. Homology-directed repair (HDR)-mediated knock-in in BFF cells was also significantly improved when cells were supplemented with pifithrin-μ, which is a small molecule that inhibits binding of p53 to mitochondria. Three pulses at 250 V resulted in the most efficient electroporation in BFF cells and 1.5 μg/ml puromycin was found to be the optimal concentration for screening. Moreover, Y-Chr-eGFP transgenic BFF cells and cloned buffalo embryos were successfully generated using CRISPR/Cas9-mediated gene editing combined with the somatic cell nuclear transfer (SCNT) technique. At passage numbers 6-8, the growth rate and cell proliferation rate were significantly lower in Y-Chr-eGFP transgenic than in non-transgenic BFF cells; the expression levels of the methylation-related genes DNMT1 and DNMT3a were similar; however, the expression levels of the acetylation-related genes HDAC1, HDAC2, and HDAC3 were significantly higher (p<0.05) in Y-Chr-eGFP transgenic BFF cells compared with non-transgenic cells. Y-Chr-eGFP transgenic BFFs were used as donors for SCNT, the results showed that eGFP reporter is suitable for the visualization of the sex of embryos. The blastocyst rates of cloned buffalo embryos were similar; however, the cleavage rates of transgenic cloned embryos were significantly lower compared with control. We hypothesize that this lower cleavage rate may be due to the change in acetylation-related gene expression in the Y-Chr-eGFP transgenic BFF cells. In summary, we optimized the protocol for generating transgenic BFF cells and successfully generated Y-Chr-eGFP transgenic embryos using these cells as donors.